-11x-8y=-6

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Add 11x to both sides of the equation.

-8y=-6+11x

Divide each term by -8 and simplify.

Divide each term in -8y=-6+11x by -8.

-8y-8=-6-8+11x-8

Cancel the common factor of -8.

Cancel the common factor.

-8y-8=-6-8+11x-8

Divide y by 1.

y=-6-8+11x-8

y=-6-8+11x-8

Simplify -6-8+11x-8.

Simplify each term.

Cancel the common factor of -6 and -8.

Factor -2 out of -6.

y=-2(3)-8+11x-8

Cancel the common factors.

Factor -2 out of -8.

y=-2⋅3-2⋅4+11x-8

Cancel the common factor.

y=-2⋅3-2⋅4+11x-8

Rewrite the expression.

y=34+11x-8

y=34+11x-8

y=34+11x-8

Move the negative in front of the fraction.

y=34-11×8

y=34-11×8

Reorder 34 and -11×8.

y=-11×8+34

y=-11×8+34

y=-11×8+34

Rewrite in slope-intercept form.

y=-118x+34

y=-118x+34

Using the slope-intercept form, the slope is -118.

m=-118

Find the Slope -11x-8y=-6